Kajian Geologi, Radiometri dan Geokimia Granit Banggai dan Formasi Bobong Untuk Menentukan Daerah Potensial Uranium di Pulau Taliabu, Maluku Utara - Ngadenin, Ngadenin (EKSPLORIUM, 2016)
Geological, radiometrical, and geochemichal studies of Banggai granites and Bobong Formation have been conducted in order to obtain potential uranium area. Taliabu island is selected for the study because Taliabu island is a micro continent fraction of the Gondwana super continent that separated at the end of the Mesozoic to Paleogene period. Some types of uranium mineralization formed in the period of Gondwana include sandstone-type, lignite coal types and vein-type. Taliabu island is a small part from the Gondwana super continent so it is expected will be found uranium mineralization or at least indications of uranium mineralization occurences. The aim of this study is to obtain uranium potential areas for the development of uranium exploration in the future. The methods used are reviewing geological, radiometric, and geochemical data from various sources. The results of review showed that geological setting, radiometric, and geochemical data gives positive indication to the formation of uranium mineralization for sandstone type. Banggai Granite is a potential uranium source. Sandstone of Bobong Formation as a potential host rock. Coal and pyrite as a potential precipitant. Potential areas for uranium is located around Bobong Formation.